Bispectral Index-Monitored Anesthesia Induction in Older Adults Undergoing Elective Surgery: Comparing Ciprofol and Propofol in a Prospective, Single-Center, Double-Blind, Randomized Controlled Study - Zou H; Xi F; Fu Y; Xu J; Zhang P; Li D; Luo H (Dove Medical Press, 2024)
Haibin Zou,1 Fangfang Xi,1 Yuanyuan Fu,1 Jinhui Xu,1 Ping Zhang,1 Dongge Li,2 Heguo Luo1 1Department of Anesthesiology, Jiangxi Provincial People's Hospital, The First Affiliated Hospital of Nanchang Medical College, Nanchang, Jiangxi, 330006, People's Republic of China; 2The Third Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, 330006, People's Republic of ChinaCorrespondence: Heguo Luo, Department of Anesthesiology, Jiangxi Provincial People's Hospital, The First Affiliated Hospital of Nanchang Medical College, Nanchang, Jiangxi, 330006, People's Republic of China, Tel +86 13807035516, Email ddjy121@163.comPurpose: Ciprofol, a new sedative anesthetic developed in China, offers rapid onset and recovery, reduced injection pain, and stable circulation. However, its effect on blood pressure during anesthesia induction in older adults remains unclear. To compare the effects of propofol and ciprofol on hypotension induced by general anesthesia in older adults.Patients and Methods: This prospective, single-center, double-blind, randomized, controlled clinical study enrolled 117 older adults undergoing surgery. Patients in the ciprofol group (group C) received an intravenous injection of ciprofol (0.3 mg/kg, n=57), while the propofol group (group P) received an intravenous injection of propofol (1.5 mg/kg, n=58). The primary outcome was the incidence of hypotension (mean arterial pressure (MAP) decreased by > 30% from baseline or MAP< 65 mmHg). Secondary outcomes included induction success rate (bispectral index (BIS) value ≤ 60 and Modified Observer's Assessment of Alertness/Sedation Scale (MOAA/S) score ≤ 1), injection pain, number of drug additions, time to BIS 60, time to eyelash reflex disappearance, blood pressure changes, incidence of hypertension, tachycardia and BIS values before and after administration.Results: The incidence of induced hypotension was 26.3% (15/57) in group C and 48.3% (28/58) in group P (OR=0.383, 95% CI:175- 0.837, P =0.015). Group C had significantly lower injection pain incidence (5.3% vs 20.7%, OR=0.213, 95% CI: 0.057- 0.801, p=0.014). Both groups had a 100% induction success rate, with no significant difference in the number of additional doses. Post-intubation hypertension and tachycardia incidence were not significantly different. Group C showed less blood pressure decrease during induction and a deeper anesthesia level.Conclusion: Compared to propofol, ciprofol reduces the incidence of induced hypotension in older adults and maintains more stable blood pressure during induction. Additionally, ciprofol reduces injection pain and provides a good depth of anesthesia, making it a safe and effective option for anesthesia induction in older adults.Trial Registration ClinicalTrials.gov Identifier: ChiCTR2200066053.Keywords: ciprofol, propofol, bispectral index, BIS, hypotension